Konsep Psikologi Pendidikan Islam Menurut Malik Badri dan Syed Naquid Al-Atthas - Zohdi Halil; Muhammad Yani; Era Mutiara Pratiwi; Gazi (Mataram University, 2026)
This study aims to analyze the concept of Islamic educational psychology from the perspective of contemporary scholars, particularly the thoughts of Syed Muhammad Naquib al-Attas and Malik Badri. The background of this study is based on the dominance of Western educational psychology which tends to be secular and materialistic, thus less accommodating the spiritual dimension in Islamic education. Therefore, it is necessary to reconstruct the concept of educational psychology based on the values of monotheism and human nature. This study uses a qualitative approach with a library research method. Data were obtained from various sources such as books, scientific journals, and relevant documents, then analyzed descriptively and analytically to find the main concepts related to Islamic educational psychology. The results show that Malik Badri emphasizes a holistic and psychospiritual psychological approach through the concept of tazkiyah al-nafs, with an integration of scriptural, philosophical, and Sufism approaches. Meanwhile, Syed Muhammad Naquib al-Attas emphasizes the importance of an Islamic worldview framework centered on monotheism through the concept of ta'dib as the basis for the formation of civilized humans. Both figures share a similar view of education as a process of developing a perfect human being encompassing intellectual, emotional, and spiritual aspects. However, they differ in their emphasis, with Badri's approach being more practical and applied, and al-Attas's more philosophical-epistemological. This study concludes that the integration of the thoughts of Malik Badri and Syed Muhammad Naquib al-Attas can provide a strong conceptual foundation for developing Islamic educational psychology relevant to the challenges of the modern era.